Structure for dependability computer-based systems from an interdisciplinary perspective - Besnard, Denis. (Springer London :, 2006)
This book breaks new ground by presenting an interdisciplinary approach to a crucial problem – system dependability. Computer-based systems include hardware, software and people. Achieving dependability for such systems requires an interdisciplinary approach. In Structure for Dependability: Computer-Based Systems from an Interdisciplinary Perspective, computer scientists, sociologists, statisticians and psychologists bring together their latest research on the structure of dependable computer-based systems. The result is a highly readable overview of ways to achieve dependability in large computer-based systems with practical advice on designing dependable systems. Work on structure for dependability has usually come from a single discipline and has been concerned only with the computer systems. Stakeholders and system designers now agree that human and social issues cannot be separated from technical matters. The approach taken in this book demonstrates that interdisciplinarity delivers real benefits in the design and deployment of complex computer-based systems. This book is one of the outcomes of a six year Interdisciplinary Research Collaboration. Topics covered include fault tolerance, system evolution, determining software specifications, HCI, architecture, certification, dependability arguments, organisations, diagrams, time and procedures. System developers, stakeholders, decision makers, policymakers and researchers will find this book a unique resource which highlights the core issues for all those involved in improving dependability in complex computer-based environments. The role of structure: a dependability perspective -- The role of structure: a software engineering perspective -- System properties -- Structuring evolution: on the evolution of socio-technical systems -- Time bands in systems structure -- Human components -- Procedures, programs and their impact on dependability -- Cognitive conflicts in dynamic systems -- Systems descriptions -- Architectural description of dependable software systems -- Computational diagrammatics: diagrams and structure -- Ethnography and the social structure of work -- Faults, errors and failures in communications: a systems theory perspective on organisational structure -- Guaranteeing Dependability -- Security implications of structure -- The structure of software development thought -- On the use of diverse arguments to increase confidence in dependability claims -- Qualitative analysis of dependability argument structure.